2021
DOI: 10.3390/cancers13164124
|View full text |Cite
|
Sign up to set email alerts
|

Pan-Cancer Analysis of Immune Complement Signature C3/C5/C3AR1/C5AR1 in Association with Tumor Immune Evasion and Therapy Resistance

Abstract: Despite the advances in our understanding of the genetic and immunological basis of cancer, cancer remains a major public health burden with an ever-increasing incidence rate globally. Nevertheless, increasing evidence suggests that the components of the complement system could regulate the tumor microenvironment (TME) to promote cancer progression, recurrence, and metastasis. In the present study, we used an integrative multi-omics analysis of clinical data to explore the relationships between the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 104 publications
(133 reference statements)
1
24
0
Order By: Relevance
“…4b ) TGM2 correlated genes were ranked based on their Z-score and mapped using the TCGA SKCM dataset in LinkedOmics database [ 27 ]. Interestingly, many genes known to be associated with the activation of immune-related cancerous processes, response to immunotherapy, and tumor immune infiltration were found to be associated with TGM2 expression like C3AR1 ( r = 0.5712, p = 2.956e-10) [ 28 ], LAIR1 ( r = 0.5612, p = 7.015e-10) [ 29 ], FCER1G ( r = 0.5588, p = 0,8553e-10) [ 30 ], SLAMF8 ( r = 0.5562, p = 1.066e-10) [ 31 ], IFI30 ( r = 0.5472, p = 2.228e-10) [ 32 ], TYROBP ( r = 0.5462, p = 2.416e-09) [ 33 ], and SIGLEC-9 ( r = 0.5442, p = 2.829e-09) [ 34 ], which were found in the top ten TGM2 positively correlated ones through two-sided Pearson’s ( R ) coefficient analysis (Fig. S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…4b ) TGM2 correlated genes were ranked based on their Z-score and mapped using the TCGA SKCM dataset in LinkedOmics database [ 27 ]. Interestingly, many genes known to be associated with the activation of immune-related cancerous processes, response to immunotherapy, and tumor immune infiltration were found to be associated with TGM2 expression like C3AR1 ( r = 0.5712, p = 2.956e-10) [ 28 ], LAIR1 ( r = 0.5612, p = 7.015e-10) [ 29 ], FCER1G ( r = 0.5588, p = 0,8553e-10) [ 30 ], SLAMF8 ( r = 0.5562, p = 1.066e-10) [ 31 ], IFI30 ( r = 0.5472, p = 2.228e-10) [ 32 ], TYROBP ( r = 0.5462, p = 2.416e-09) [ 33 ], and SIGLEC-9 ( r = 0.5442, p = 2.829e-09) [ 34 ], which were found in the top ten TGM2 positively correlated ones through two-sided Pearson’s ( R ) coefficient analysis (Fig. S 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In cancer, the complement system was found to exert a critical anti-tumor function by inducing cell cytotoxicity either directly (complement-dependent cytotoxicity, CDC) or indirectly through antibodies (antibody-dependent cell-mediated cytotoxicity, ADCC), the latter being relevant in antibody-based immunotherapy ( 44 , 45 ). However, recent studies have demonstrated the expression of complement components C3 and C5 and the anaphylatoxins C3a and C5a in several types of tumors ( 12 , 14 , 46 ) and their role in promoting tumor growth ( 46 , 47 ), angiogenesis, metastasis ( 48 , 49 ), immunosuppression, inhibition of T-cell responses ( 14 , 50 ), and regulatory cell recruitment [myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs)] ( 51 , 52 ). Moreover, C3 expression correlated in resistance to PD-L1 antibody treatment in a mouse model of B16F10 and CT26 tumors ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have demonstrated in TMEs increased concentrations of complement components that, by affecting immune cell responsiveness, contribute to tumor progression ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Lawal et al. reported that C3AR1 was associated with tumor immune evasion, prognosis, and immunotherapy in melanoma, colorectal, brain, breast, stomach, and renal cancer ( 52 ). We speculated that C3AR1 may play a similar role in tumor immunity and promoting the development of ESCC.…”
Section: Discussionmentioning
confidence: 99%